Alterations of the L-Forms of a Sporebearing Bacillus - Dienes, Louis (1970)
A large pleomorphic gram-negative bacillus developed as a contaminant on blood-agar. Spores were formed in one culture. L-forms were produced with penicillin on blood-agar with 2.5% NaCl; they grew well when transplanted to agar with 0.5% NaCl. After several transplants and long incubation of the L-forms without penicillin, in three transplants small gram-negative pleomorphic bacilli grew, but no L-forms. This occurred once on blood-agar and twice on 30% gelatin. The growth obtained from these small bacilli was similar in morphology and in the physical properties of the organisms to the altered L-forms of Proteus and Salmonella. Multiplication of the pleomorphic organisms and development of branching filaments from the round forms was apparent. The original large gram-negative bacillus was regularly recovered from the L-forms, and was recovered several times from the descendants of the small bacilli. These observations are essentially similar to those made with L-forms of Proteus and with an L-form studied in 1952, indicating alterations in L-forms of bacteria which do not produce B type L-forms.